MENUMBUHKAN SIKAP TOLERANSI BERAGAMA MELALUI KEGIATAN GOTONG ROYONG DI DESA KUTA JUNGAK - Gustina Permatasari Ritonga; Ayu Amaliah; Nanda Qurrota Annisa Limbong; Muhammad Ikhsan (LPPM Universitas Bina Bangsa, 2023)
Tolerance is an attitude of mutual respect and respect for the various differences in society. The differences that exist can be seen from ethnicity, culture, language, and religion. In religion, it is very necessary to have tolerance between adherents of one religion and another. Religious tolerance is an attitude where everyone from a different religion respects all adherents of other religions. Mutual assistance activities are considered capable of being a medium for mobilizing and generating a sense of community solidarity as well as being able to create a life that upholds social values. The author conducted this research to investigate the role of cooperation activities in efforts to foster attitudes of religious tolerance between Muslim and Christian communities in Kuta Jungak Village. The author uses a descriptive qualitative approach with data collection techniques in the form of observation and documentation. The research that has been carried out shows that the mutual assistance activities carried out have great potential in building attitudes of religious tolerance. The mutual assistance carried out in this village has proven to influence the growth of a sense of religious tolerance